Effect of Sub- Chronic Administration of Omeprazole on Hematological and Biochemical Parameters in Fischer Male Rats - Samia Elkedrawy; Alaa Aldouayb; Akraam Areebi; Abdalmohymen Shuqman; Bushra Aboukhadeer (AlQalam Journal of Medical and Applied Sciences, 2024)
Long-term use of proton pump inhibitors (PPIs) is believed to have various potential adverse events. Omeprazole is a part of PPIs most commonly prescribed worldwide; it irreversibly binds to the H+-K+ ATPase enzyme system in the gastric parietal cells to reduce the secretion of H+ ions into the lumen of the stomach. The main objective of the current work is to assess the adverse effects of omeprazole medication on certain hematological and biochemical parameters in rats who were on treatment for three months. We conducted a comparative cross-sectional study between March 2024 and July 2024. 20 male Fischer rats (Albino) aged two months, weighting (200-250g) was obtained from the animal house located in the Libyan center for medical research, in the city of Alzawia, and were enrolled in this study. Rats were divided into two groups, the first group was the control (Normal saline group) (n=10), second was administered 40mg/kg omeprazole via IP route (n=10) once daily. Complete blood count and biochemical parameters were measured for both groups. The treatment group had remarkably significant reductions in the number of red blood cells (RBCs) (p<0.001) and the platelets indices. Omeprazole elevated the cholesterol level (p<0.001) and triglyceride (p<0.001) as well as low-density lipoprotein (p<0.01). However, no impact was found with high density lipoprotein (HDL) (p>0.05). Blood urea levels (p<0.001) were significantly increased in the treatment group treated with omeprazole medication. The results also showed that the treatment group had a significant decline in calcium levels (p<0.001) than that of the control group. Prolonged use of omeprazole might result in adverse effects on hematological profile, particularly RBCs and their indices leading to the development of anemia in patients on this medication. Furthermore, it might result in disturbances in biochemical profile, levels of minerals, and vitamins as consequences of affected absorption. يُعتقد أن الاستخدام طويل الأمد لمثبطات مضخة البروتون له العديد من الآثار الجانبية المحتملة. أوميبرازول هو جزء من مثبطات مضخة البروتون الأكثر شيوعًا في جميع أنحاء العالم؛ فهو يرتبط بشكل لا رجعة فيه بنظام إنزيم H+-K+ ATPase في الخلايا الجدارية المعدية لتقليل إفراز أيونات H+ في تجويف المعدة. الهدف الرئيسي من العمل الحالي هو تقييم الآثار الجانبية لدواء أوميبرازول على بعض المعايير الدموية والكيميائية الحيوية في الفئران التي كانت تتلقى العلاج لمدة ثلاثة أشهر. أجرينا دراسة مقارنة مقطعية بين مارس 2024 ويوليو 2024. تم الحصول على 20 فأرًا ذكرًا من نوع فيشر (ألبينو) بعمر شهرين، بوزن (200-250 جرامًا) من بيت الحيوانات الواقع في المركز الليبي للأبحاث الطبية بمدينة الزاوية، وتم تسجيلهم في هذه الدراسة. تم تقسيم الفئران إلى مجموعتين، المجموعة الأولى كانت المجموعة الضابطة (مجموعة المحلول الملحي العادي) (ن = 10)، المجموعة الثانية تم إعطاؤها 40 مجم / كجم من أوميبرازول عن طريق الحقن داخل الصفاق (ن = 10) مرة واحدة يوميًا. تم قياس تعداد الدم الكامل والمعايير الكيميائية الحيوية لكلا المجموعتين. أظهرت مجموعة العلاج انخفاضًا ملحوظًا في عدد خلايا الدم الحمراء (P <0.001) ومؤشرات الصفائح الدموية. رفع أوميبرازول مستوى الكوليسترول (P <0.001) والدهون الثلاثية (P <0.001) وكذلك البروتين الدهني منخفض الكثافة (P <0.01). ومع ذلك، لم يتم العثور على أي تأثير مع البروتين الدهني عالي الكثافة (p>0.05). ارتفعت مستويات اليوريا في الدم (p<0.001) بشكل ملحوظ في مجموعة العلاج التي عولجت بدواء أوميبرازول. أظهرت النتائج أيضًا أن مجموعة العلاج شهدت انخفاضًا كبيرًا في مستويات الكالسيوم (p<0.001) مقارنة بمجموعة التحكم. قد يؤدي الاستخدام المطول لأوميبرازول إلى آثار ضارة على الملف الدموي، وخاصة خلايا الدم الحمراء ومؤشراتها مما يؤدي إلى تطور فقر الدم لدى المرضى الذين يتناولون هذا الدواء. علاوة على ذلك، قد يؤدي ذلك إلى اضطرابات في الملف الكيميائي الحيوي ومستويات المعادن والفيتامينات نتيجة لتأثر الامتصاص